Tanggung Jawab Negara Myanmar atas Kejahatan terhadap Kemanusiaan pada Etnis Rohingya - Velinthia Latumahina (Journal of Comprehensive Science, 2026)
Crimes against humanity experienced by the Rohingya ethnic group in Myanmar constitute one of the most serious human rights violations in contemporary international law. Systematic acts of violence such as killings, forced displacement, torture, and discrimination carried out by state apparatuses as well as certain groups indicate a pattern of structured and widespread violations. This study aims to analyze the responsibility of the State of Myanmar from the perspective of international law, particularly based on the principle of state responsibility and international human rights norms. The research method employed is a normative juridical method with statutory and conceptual approaches. The data used consist of primary legal materials such as international conventions, decisions of international courts, and reports of international institutions, as well as secondary legal materials in the form of scientific literature and legal journals. The results of the study indicate that Myanmar can be held internationally responsible for failing to protect its citizens and is alleged to have been directly involved in crimes against humanity. Such actions are contrary to international obligations, including the principles of non-discrimination, protection of minorities, and the prohibition of serious international crimes. Furthermore, mechanisms of accountability may be pursued through international forums such as the International Court of Justice (ICJ) and the International Criminal Court (ICC), although various juridical and political obstacles remain. In conclusion, the State of Myanmar bears international legal responsibility for the violations committed against the Rohingya ethnic group. Therefore, an active role of the international community is required to promote law enforcement, provide protection to victims, and ensure that similar crimes do not recur in the future